Les regards des Nord-Américains portés sur les cultures pueblo et navajo. Une histoire de cultures ou la culture de l'histoire ? - Estelle Brun (Belgeo)
This article approaches the gaze focused on minority cultures, the Pueblos and Navajos tribes, through their associated heritage. The Native American sites inscribed on the World Heritage List, Chaco Culture (Chaco Canyon and Aztec Ruins), Mesa Verde and Taos Pueblo (Vth-XIVth c.) have the distinction of being linked to living cultures, whose representatives have kept memory of the places enlivened by the presence of their ancestors, through oral traditions. As such, with the implementation of the NAGPRA law, these heritage, also classified as National Parks, with the exception of Taos Pueblo, were therefore officially affiliated with existing tribes living in the Four Corners region (Utah, Colorado, New Mexico and Arizona). These states are inhabited by populations who have rarely migrated in more than a millennium, whose numerous culturally affiliated remains and oral traditions legitimize their belonging to these territories; they are in consequence faced with multiple issues that extend far beyond the simple economic phenomenon more often than not associated with tourism. Thereby, dealing with the Anglo-American’s heritage gazes on these cultures, pueblo and Navajo, aims to highlight the multiple dimensions of this heritage development, at every scale. In the current context of globalization, it seems that the evolution of the gazes associated to Native American heritage is accompanied by an evolution of intercultural relations in the extended heritage territory.This study focuses on Anglo-American actors, tourists and professionals associated with these heritage sites, as well as on the Pueblo and Navajo Indians and the "different" gaze they have of their own heritage. Additionally, it aims to understand how the heritage and the imaginary associated with it can interfere with a culture, allowing or not its cultural revitalization and the "rewriting" of its history.